Cloning of gene encoding the vegetative insecticidal protein (Vip3) from Bacillus thuringiensis - Ngọc Phạm Bích; Ngọc Lê Thị Hồng; Trà Phạm Thị; Hà Chu Hoàng; Bình Lê Trần (Vietnam Journal of Biotechnology, 2008)
Journal of Biotechnology 3(1): 99-104, 2005